Entrepreneurial Orientation and Product Innovation. The Moderating Role of Family Involvement in Management - Fredyna, Taras; Ruiz-Palomo, Daniel; Dieguez-Soto, Julio (European Journal of Family Business, 2019)
In this current research it has been examined, firstly, the Entrepreneurial orientation in relation with Product innovation, Incremental innovation and Radical innovation, and, secondly, the moderating effect of Family involvement in the management of companies in the relationship between Entrepreneurial orientation and Product innovation, Incremental innovation and Radical innovation. Using a sample of 634 Spanish family firms, the results found conclude that the Entrepreneurial orientation has a positive effect on Product innovation, Incremental innovation and Radical innovation, and moreover, they reveal that the Family involvement in the management of companies has a moderating effect on these relations, witnessing that family firms with higher scale of Family involvement in the management of the companies reduces the effect of Entrepreneurial orientation on Product innovation, Incremental innovation and finally, Radical innovation.